Pembuatan Alat Uji Tarik Universal Statis Dengan Penggerak Servomotor Berkapasitas Maksimum 1 kN - Feberius Gea; Rakhmad Arief Siregar; M. Yusuf Rahmansyah Siahaan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
Tensile test is one of several tests that are commonly used to determine the mechanical properties of a material. The purpose of this research is to build and assemble products according to customer needs and to be able to analyze the process of making a static universal tensile tester with a servomotor drive with a capacity of 1 kN. It is hoped that this research can facilitate the selection of raw materials in providing information about the materials to be used and used. This tensile test equipment with a capacity of 1 kN uses a servomotor as the main driver. This type has begun to be used in the world because it is simpler than other motors, so this tool can compete with tensile test equipment sold in the market. This tool is equipped with supporting components such as a load cell, encoder and control panel using a data cable so that it gets graphic results when testing using visual studio software.